2018
DOI: 10.1007/s12192-018-0893-2
|View full text |Cite
|
Sign up to set email alerts
|

Scopoletin intervention in pancreatic endoplasmic reticulum stress induced by lipotoxicity

Abstract: Endoplasmic reticulum (ER), a dynamic organelle, plays an essential role in organizing the signaling pathways involved in cellular adaptation, resilience, and survival. Impairment in the functions of ER occurs in a variety of nutritive disorders including obesity and type 2 diabetes. Here, we hypothesize that (scopoletin) SPL, a coumarin, has the potential to alleviate ER stress induced in vitro and in vivo models by lipotoxicity. To test this hypothesis, the ability of SPL to restore the levels of proteins of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Previous studies have confirmed that some of the above ingredients have abilities of the regulation of ER stress. For instance, the intervention of scopoletin, 41 caffeic acid, 42 and chlorogenic acid 43 could alleviate the endoplasmic reticulum stress induced by high-fat diet, glycated low-density lipoproteins and palmitic acid, respectively. Thus, it was plausible that the inhibition of ER stress is involved in the protection of CS against cell apoptosis and vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that some of the above ingredients have abilities of the regulation of ER stress. For instance, the intervention of scopoletin, 41 caffeic acid, 42 and chlorogenic acid 43 could alleviate the endoplasmic reticulum stress induced by high-fat diet, glycated low-density lipoproteins and palmitic acid, respectively. Thus, it was plausible that the inhibition of ER stress is involved in the protection of CS against cell apoptosis and vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…This coumarin lowered postprandial hyperglycemia through inhibition of carbohydrate digestive enzymes, e.g., α-glucosidase and α-amylase (Jang et al 2018). Kalaivanan et al (2018a) exhibited that 9 intervention could suppress pancreatic endoplasmic reticulum stress (normally observed in type 2 diabetes sufferers) induced by lipotoxicity and revealed its potential in delaying the progression of insulin resistance. The same group also showed that supplementation of 9 could improve insulin sensitivity in rats by attenuating the imbalance of insulin signaling through 5 0 -adenosine-monophosphate-activated protein kinase (Kalaivanan et al 2018b).…”
Section: Antidiabeticmentioning
confidence: 96%
“…ER stress markers, such as glucose regulated protein 78 (GRP78), protein kinase like endoplasmic reticulum kinase (PERK), inositol requiring enzyme 1 (IRE1), X box-binding protein1 (XBP1), and C/EBP homologous protein (CHOP) were found to be elevated in the pancreas of high-fat/highfructose-fed rats [17]. Similarly, the expression of ER stress-related proteins, including IRE1, PERK, and activating transcription factor 6 (ATF6) were increased in the pancreatic tissue of high-fat/high-fructose-fed rats [52]. Also, it was determined an increase in oxidative parameters, including CAT, glutathione (GSH), and MDA as well as ER stress-related proteins such as binding immunoglobulin protein (BIP) and CHOP in the pancreas of rats fed with a high-fat/high-fructose diet from birth to young adulthood [18].…”
Section: The Effects Of High-fructose Diet On Cellular Stress In Panc...mentioning
confidence: 99%